Nanosecond high current and high repetition rate electron source - Gushenets V. I.; Koval N. N. Nikolay Nikolaevich; Schanin P. M.; Tolkachev V. S. (1996, 1996)
A broad electron beam source with a plasma hollow cathode has been developed which is intended for production of nanosecond electron beams with a high repetition rate. The source lifetime is over 109 shots. To reduce the operating pressure and shorten the time required for the formation of plasma in the cathode cavity, an auxiliary triggering glow discharge with a hollow cathode is used. With an accelerating voltage of 40 kV a pulse repetition rate of 50-1000 Hz, and a pulse duration of 100 ns, an electron beam of current up to 200 A and risetime 25 ns has been produced.